2019
DOI: 10.1101/688366
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NMDAR-dependent emergence of behavioral representation in primary visual cortex

Abstract: Neocortical sensory areas are generally thought to faithfully represent external stimuli. However, a growing body of evidence suggests that cortical networks exhibit considerable functional plasticity over multiple temporal scales, allowing them to modify their output to reflect ongoing behavioral demands. Nevertheless, the dynamics of sensory and non-sensory representations during acquisition of stimulus-guided behavior are not well understood. We performed longitudinal 2-photon imaging of activity in primary… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
4
1
Order By: Relevance
“…The stimulus-choice associations that animals were trained on were not reflected in the cotuning preferences of single cells (Fig 4). This was surprising in light of previous studies (Poort et al 2015, Puscian et al 2020), in which coherence between visual encoding and behavioral response emerged over training. There are a number of differences in these tasks that could account for these differences.…”
Section: Discussioncontrasting
confidence: 63%
“…The stimulus-choice associations that animals were trained on were not reflected in the cotuning preferences of single cells (Fig 4). This was surprising in light of previous studies (Poort et al 2015, Puscian et al 2020), in which coherence between visual encoding and behavioral response emerged over training. There are a number of differences in these tasks that could account for these differences.…”
Section: Discussioncontrasting
confidence: 63%
“…Notably, we did not find similarly strong representation of sensory information in mesoscopic network activity, although this may reflect a lack of behavioral relevance for the stimuli as presented here. We and others have shown that training can modify the sensory and motor representations by single cortical neurons 12,[40][41][42] , and future studies must determine if sensory inputs that gain salience through experience are differentially encoded by large-scale cortical dynamics.…”
Section: Dynamic Functional Connectivity Suggests Distinct Cortical Subnetworkmentioning
confidence: 94%
“…However, this result may also reflect a lack of behavioral relevance for the stimuli as presented here. We and others have shown that training can modify the sensory and motor representations by single cortical neurons ( 14, 47-49 ), and future studies must determine if development, experience, or learning produce functional reorganization of large-scale networks.…”
Section: Dynamic Functional Connectivity Suggests Distinct Cortical S...mentioning
confidence: 97%
“…Finally, in the context of perceptual learning, it has been demonstrated that repeated presentation of grating stimuli can induce gain changes in cortical responses over many days during the performance of visual perception tasks [56,57]. Passive stimulus viewing alone may be sufficient to induce perceptual learning and incite changes for both gratings and natural stimuli [58,59], possibly with differences across stimuli.…”
Section: Differences In Rdi Between Stimuli Are Not Explained By Stimulus Temporal Structurementioning
confidence: 99%